Environmental regulation promotes green development in China: from the perspective of technological innovation - Hao, Feng; Zang, Yuan; Fan, Bokai; Zhang, Yuan (Frontiers in Energy Research, 2023)
Based on panel data of 286 prefecture-level cities in China, this study analyzes the direct impact of environmental regulation and its classified policies on green development, while exploring the indirect effects and threshold effects of technological innovation in the green development effect of environmental regulation. There are four main findings in this study. (1) The impact of environmental regulation on green development follows a U shaped pattern and its mode varies with the type of environmental regulation and the type of cities. (2) Environmental regulation can promote green development through technological innovation, and the industrial structure has a positive moderating effect. (3) Technological innovation is a threshold variable in the impact of environmental regulation on green development: when technological innovation surpasses the threshold value, the green development effect of environmental regulation changes from negative to positive. Therefore, governments should strengthen environmental regulation, effectively play the driving role of different environmental regulation policies, and transform the development driving force through strengthened technological innovation to achieve regional green development.